Minsky, Veblen, and the endogeneity of the capitalism crises: A comparative analysis between Minsky and Veblen - Montani Martins, Norberto; Chaves Drach, Daniel (Brazilian Keynesian Review, 2021)
This paper aims at analyzing economic crises from the viewpoint of Minsky's and Veblen's analytical frameworks. We aim at understanding how both authors build their theories of crisis as endogenous processes to capitalism dynamics and identifying the main building blocks of each approach. We present the convergences and divergences between Minsky and Veblen, stressing that, despite having different theoretical basis, the analyses of both authors have many points of contact, which permit us to stablish a dialogue between them. The evolutionary nature of economic processes and the role of temporality and uncertainty in both approaches are highlighted as the main points of convergence. At the end, we argue that the Minskyian framework consists in a refinement of the analysis of crises as endogenous phenomena of capitalism and an incorporation of institutionalist features into its theory reinforces this framing.